Anode interfacial modification for non‐fullerene polymer solar cells: Recent advances and prospects - Ahmad, Nafees; Liang, Guangxing; Fan, Ping; Zhou, Huiqiong (InfoMat, 2022)
Recently, the power conversion efficiency (PCE) of single‐junction non‐fullerene polymer solar cells (NF‐PSCs) has surpassed 19% due to the fast development of novel donor polymers, NF‐acceptors, device engineering, and interlayer materials. The anode interlayer (AIL) plays a vital role in improving the efficiency and stability of PSCs. The challenges and opportunities in this research area encourage researchers to pursue great innovation in developing new materials and strategies for highly efficient NF‐PSCs. This review summarizes the recent development of AIL materials and their modification strategies in single‐junction NF‐PSCs. Firstly, a brief introduction, key functions, basic requirements, and peculiar features of AILs when employed in NF‐PSCs are discussed. Then, the impact of AIL materials (including organic, inorganic, and hybrid materials) on the PCE and the stability of NF‐PSCs are described. Afterward, the fabrication of large‐area devices and related issues are highlighted. The summary and the future challenges regarding efficient AIL are summarized in the last section of this review. This review summarizes the recent development of anode interlayer (AIL) materials and their modification strategies in single‐junction non‐fullerene polymer solar cells (NF‐PSCs). The discussion includes the importance, key requirements, and peculiar functions of AIL in NF‐PSCs as well as the impact of several AIL materials and strategies on the performance of single‐junction NF‐PSCs. The large area devices, related issues, and future challenges are also discussed.